Pengembangan Media Pembelajaran Interaktif dengan Pendekatan Pembelajaran Mendalam (Deep Learning) pada Materi Pajak Penghasilan (Pph) Pasal 21 untuk Siswa SMK Negeri di Surabaya (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This research aims to develop interactive learning media using a deep learning approach for income tax article 21 material for public vocational high school students in Surabaya. The background of this research stems from preliminary studies indicating that the learning media currently in use are limited, and the complex nature income tax article 21 material makes it difficult for students to grasp. This study is a research and development (R&D) projectusing the ADDIE model (analysis, Design, Development, Implementation, Evaluation). The developed product is an android application with the following main features: learning material, instructional videos, simulations, user guides, developer profiles, and reflections. The contens expert validation yielded a score of 93%, categorized as “highly suitable”, and the media expert validation reached 98%, also categorized as “highly suitable”. A limited trial was conducted with 20 eleventh-grade accounting students from four public vocational school in Surabaya.the result show that this learning medium received an 85% response rate from students, which is classified as excellent. Thus, the development of an interactive learning medium using a deep learning approach for the material on income tax article 21 has proven effective in supporting deep learning through the use of technology.